Acute Citrulline-Malate Supplementation Increases Total Work in Short Lower-Body Isokinetic Tasks for Recreationally Active Females During Menstruation - Gills, Joshua L; Spliker, Blake; Glenn, Jordan M; Szymanski, David; Romer, Braden; Lu, Ho-Cheng; Gray, Michelle (Journal of strength and conditioning research, 2023)
Gills, JL, Spliker, B, Glenn, JM, Szymanski, D, Romer, B, Lu, H-C, and Gray, M. Acute citrulline-malate supplementation increases total work in short lower-body isokinetic tasks for recreationally active females during menstruation. J Strength Cond Res 37(6): 1225-1230, 2023-Citrulline-malate (CM) exhibits acute ergogenic benefits through nitric oxide production (NO) and augmentation of vasodilatory properties. Nitric oxide is upregulated by estrogen and may influence CM's ergogenic efficacy in women. Therefore, the objective of this study was to evaluate the acute effects of CM supplementation on lower-body isokinetic performance in recreationally active women. Nineteen women (23.5 ± 3.1 years; 164.8 ± 7.0 cm; 61.9 ± 27.4 kg; 28.8 ± 8.1% body fat) completed 2 randomized, double-blind, crossover trials consuming CM (8 g CM + 12 g dextrose) or placebo (12 g dextrose). For testing trials, subjects were in the menstruating portion of the follicular phase of their menstrual cycle. Subjects performed a 5-repetition isokinetic leg extension protocol (5RP) followed by a 50-repetition isokinetic leg extension protocol (50RP), 60 minutes after supplement consumption. Repeated measures analysis of variance analysis showed that CM significantly increased total work completed, relative total work, and total work during maximum repetition compared with placebo ( p < 0.05); but no significant performance differences existed between trials for peak torque production ( p = 0.14) for the 5RP. No significant differences were identified between trials for peak torque production ( p = 0.69 ) or total work ( p = 0.33) completed during the 50RP. CM increased total work completed during the 5RP, but provided no ergogenic benefit during the 50RP in recreationally active menstruating women. CM amplifies power-based resistance exercise performance in women during the follicular phase of the menstrual cycle, potentially because of depressed estrogen levels. Additional research is needed to identify timing efficacy of CM to increase sport performance during each phase of the menstrual cycle.